USING MODELS@RUN.TIME TO MANAGE ULTRA-LARGE-SCALE SYSTEMS. - Cheng, Betty H. C. (Computer (00189162), 2009)
The article describes the challenges being posed by ultra-large-scale (ULS) system and adaptive systems for those who are working in the area of models@run.time. It cites complexity and uncertainty as the two ULS factors that pose significant needs for the research community to address. The challenging set of tasks facing a ULS system designer and the limitation of current software development environments to address such issues are also discussed.